Utvärdering av utbildning om attityder och beteenden inom ETTdemo-projektet - Berglund, Erik (2014)
This is a thesis report from SLU in Skinnskatteberg, the Swedish university of agricultural sciences. This study is an evaluation of a course in attitudes and behavior for participants of the ETT- project led by Skogforsk, the forestry research institute of Sweden. They do research for the benefit of Swedish forestry. The ETT-project is a project where there are both 74 tons ST-trucks and 90 tons ETT-trucks in test on the public roads. This study is concentrated on the ST-trucks and their drivers, company owners and logistics managers.